ANALISIS KEMAMPUAN MENCERITAKAN KEMBALI TEKS BACAAN PADA MAHASISWA ANGKATAN 2022 PRODI PENDIDIKAN BAHASA MANDARIN - Winarti, Wiwin; Veronica, Tjen; Afrimonika, Yoanna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
When learning Mandarin, speaking is the main skill that must be mastered, because through speaking we can communicate and convey information directly to others. However, in order to speak Mandarin accurately, students must practice speaking in the right way. when practicing speaking Mandarin, students often face several difficulties, namely pronunciation must be clear and intonation must be correct because otherwise the meaning will be different. Mandarin vocabulary and grammar are also difficult to learn, so students need the right way to practice their speaking skills. Retelling is one of the oral expression skills. Students can retell what they have heard or read. Retelling exercises help develop students' ability to think directly in Mandarin, improve their language skills, and enhance their oral fluency and accuracy. This research aims to determine the ability to retell reading texts by students of the 2022 batch of the Mandarin Language Education Study Program, FKIP UNTAN. The subject of this study was 26 student. The research uses quantitative research methods. Data were collected using an oral retelling test. The results of the study stated that students' ability to retell reading texts was classified as good with an average score obtained by students reaching 82.38%, and of the seven aspect of retelling the aspect that students master the most is vocabulary and the least master is detail and fluency. After being analysis, the author found that students already have good abilities in retelling reading texts.